AGROINDUSTRIAL PARK IN SYSTEM OF THE AGROFOOD MARKET - Alexander S. Nechitaylov (Вестник Северо-Кавказского федерального университета)
Development of cooperation in infrastructure of the food market, activity of small forms of managing and dairy and meat animal husbandry, their role and a place in formation of the food market is considered. The directions of effective development of the food market with participation of agroindustrial parks are offered.